2008
DOI: 10.1021/ja801947e
|View full text |Cite
|
Sign up to set email alerts
|

A One-Step Highly Sensitive Method for DNA Detection Using Dynamic Light Scattering

Abstract: A one-step homogeneous DNA detection method with high sensitivity was developed using gold nanoparticles (AuNPs) coupled with dynamic light scattering (DLS) measurement. Citrate-protected AuNPs with a diameter of 30 nm were first functionalized with two sets of single-stranded DNA probes and then used as optical probes for DNA detection. In the presence of target DNA, the hybridization between target DNA and the two nanoparticle probes caused the formation of nanoparticle dimers, trimers, and oligomers. As a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
140
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 16 publications
3
140
0
3
Order By: Relevance
“…Therefore, our method showed an ultra-wide detection range from 10 fM to 100 nM, which was wider than the values obtained by other methods. 2,5,16,26 In addition, the fluorescence intensity signal change (F -F0) increased proportionally with the concentrations of target DNA in the 1 to 100 nM range (inset in Fig. 1 based on a 3α/slope, which was better than, or comparable to, the values obtained by other methods (Table S2).…”
Section: Rapid Communicationssupporting
confidence: 48%
See 1 more Smart Citation
“…Therefore, our method showed an ultra-wide detection range from 10 fM to 100 nM, which was wider than the values obtained by other methods. 2,5,16,26 In addition, the fluorescence intensity signal change (F -F0) increased proportionally with the concentrations of target DNA in the 1 to 100 nM range (inset in Fig. 1 based on a 3α/slope, which was better than, or comparable to, the values obtained by other methods (Table S2).…”
Section: Rapid Communicationssupporting
confidence: 48%
“…[2][3][4][5] These methods can be broadly classified into two main categories: indirect detection approaches by template replication amplification and direct detection approaches by detecting original DNA. The indirect detection approaches, such as the polymerase chain reaction (PCR), loop-mediated isothermal amplification (LAMP), 6 rolling-cycle amplification (RCA), 7 and nucleic acid sequence-based amplification (NASBA), 8 increase the risk of cross-contamination from amplicons and are prone to false positives arising by artifactual amplification.…”
mentioning
confidence: 99%
“…We and many other groups have previously demonstrated that DLS can be used as a very convenient and powerful tool to monitor specific binding and non-specific adsorption of proteins to spherical gold nanoparticles [28][29][30][31]. Based on the nanoparticle size change, we and others have developed a novel platform technology, nanoparticle-enabled dynamic light scattering assay (NanoDLSay™) for biological and chemical detection and analysis with high to ultrahigh sensitivity and excellent reproducibility [32][33][34][35][36][37][38]. In this work, we applied the DLS technique to study the gold nanorods and nanorod-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic light scattering (DLS), a technique used routinely for determination of particle size and size distribution, has also been adopted for particle agglutination-based assays. [11][12][13] Recently, a washing-free one-step homogeneous assay protocol was implemented using gold nanoparticles by measuring the hydrodynamic diameter of the nanoparticle aggregates with a DLS instrument, and a detection limit of 0.5 ng/ml for mouse IgG was achieved. 12 However, DLS instruments are relatively delicate and sensitive to temperature, which may limit its applications in point-of-care testing and hinder its integration with microfluidic chip.…”
Section: Introductionmentioning
confidence: 99%